Glutathione transferase Omega 1 is required for the lipopolysaccharide-stimulated induction of NADPH oxidase 1 and the production of reactive oxygen species in macrophages - Menon, Deepthi; Coll, Rebecca; O׳Neill, Luke A.J.; Board, Philip G. (Free radical biology & medicine, 2014)
Bacterial lipopolysaccharide (LPS) stimulation of macrophages and inflammation via the Toll-like receptor 4 (TLR4) signaling pathway through NF-κΒ generates reactive oxygen species (ROS) and proinflammatory cytokines such as IL-1β, IL-6, and TNFα. Because glutathione transferase Omega 1-1 (GSTO1-1) can catalyze redox reactions such as the deglutathionylation of proteins and has also been implicated in the release of IL-1β we investigated its role in the development of LPS-mediated inflammation. Our data show that shRNA knockdown of GSTO1-1 in macrophage-like J774.1A cells blocks the expression of NADPH oxidase 1 and the generation of ROS after LPS stimulation. Similar results were obtained with a GSTO1-1 inhibitor. To maintain high ROS levels during an inflammatory response, LPS stimulation causes the suppression of enzymes such as catalase and glutathione peroxidase that protect against oxidative stress. The knockdown of GSTO1-1 also attenuates this response. Our data indicate that GSTO1-1 needs to be catalytically active and mediates its effects on the LPS/TLR4 inflammatory pathway upstream of NF-κΒ. These data suggest that GSTO1-1 is a novel target for anti-inflammatory intervention. [Display omitted] •GSTO1-1 regulates LPS-stimulated reactive oxygen species generation via TLR4.•GSTO1-1 decreases global protein glutathionylation levels in J774.1A macrophages.•NF-κB nuclear translocation is blocked in GSTO1-1-deficient J774.1A cells.